Rapid Determination of Macrolide and Lincosamide Resistance in Group B Streptococcus Isolated from Vaginal-Rectal Swabs - Wilfred P. Dela Cruz; Joann Y. Richardson; Judith M. Broestler; Jennifer A. Thornton; Patrick J. Danaher (Hindawi Limited, 2007)
Objective. Our objective was to assess the ability of real-time PCR to predict in vitro resistance in isolates of group B streptococcus (GBS). Methods. The first real-time PCR assays for the genes known to confer resistance to erythromycin and clindamycin in GBS were developed. Three hundred and forty clinical GBS isolates were assessed with these assays and compared with conventional disk diffusion. Results. The presence of an erythromycin ribosome methylation gene (ermB or ermTR variant A) predicted in vitro constitutive or inducible resistance to clindamycin with a sensitivity of 93% (95% CI 86%-97%), specificity of 90% (95% CI 85%-93%), positive predictive value of 76% (95% CI 67%-84%), and negative predictive value of 97% (95% CI 94%-99%). Conclusion. This rapid and simple assay can predict in vitro susceptibility to clindamycin within two hours of isolation as opposed to 18-24 hours via disk diffusion. The assay might also be used to screen large numbers of batched isolates to establish the prevalence of resistance in a given area.